A randomised controlled trial assessing the efficacy and safety of repeated tegaserod therapy in women with irritable bowel syndrome with constipation. Issue 12 (14th July 2005) - Tack, J; Müller-Lissner, S; Bytzer, P; Corinaldesi, R; Chang, L; Viegas, A; Schnekenbuehl, S; Dunger-Baldauf, C; Rueegg, P
Abstract : Background: It has been proposed that treatments for irritable bowel syndrome with constipation (IBS-C) should provide rapid symptomatic relief, be intermittent, and effective upon repeated use. Aims: To evaluate the efficacy and safety of tegaserod on IBS symptoms, and its impact on quality of life and health economic measures. Patients: Women (⩾18 years of age) with IBS-C according to the Rome II criteria. Methods: Prospective, double blind, placebo controlled, randomised trial. Women with IBS-C either received tegaserod 6 mg twice daily or placebo for one month. Patients with at least a partial response entered a treatment free interval. Upon symptom recurrence, tegaserod treated patients were re-randomised to tegaserod or placebo for an additional month. Primary efficacy variables were response (overall IBS symptoms and abdominal discomfort/pain) to first and repeated treatment. Analysis was by intention to treat. Results: 2660 patients and 1191 patients were randomised for first and repeated treatment respectively. Tegaserod was superior to placebo for each primary efficacy variable (first treatment: 33.7% v 24.2% responders respectively for relief of IBS symptoms and 31.3% v 22.1% for relief of abdominal discomfort/pain; repeated treatment: 44.9% v 28.7%, and 42.4% v 27.1%, all p<0.0001). Tegaserod was superior to placebo for every secondary efficacy variable (relief of abdominal discomfort/pain, bloating and constipation; stool frequency and consistency). A response to tegaserod was observed within the first treatment week. Tegaserod produced greater satisfaction, work productivity, and improved quality of life than placebo (p<0.05). Conclusion: Tegaserod provides rapid and sustained relief of IBS-C symptoms both during first and repeated treatment.